THE EFFECT OF USING QUESTIONING STRATEGIES ON STUDENTS’ READING COMPREHENSION - Hana Julianty Ginting; Berlin Sibarani (Universitas Negeri Medan, 2016)
This study aims at investigating the effect of Questioning Strategies on students’ reading comprehension in narrative text. This study was conducted by using experimental research design. The population of the study was the students of grade VIII of SMP Negeri 5 Tebing Tinggi in the academic year 2015/2016, which consisted of 9 parallel classes. Two classes were taken as the sample by applying lottery technique and each groups consisted of 30 students. The sample was divided into two groups. The class VIII-5 was experimental group and class VIII-7 was control group. The Experimental group was taught by applying questioning strategies; otherwise the control group was taught by using conventional strategy. The data of the study were obtained by objectives test. To determine the reliability of the test, KR-20 formula was used. The data calculation showed that the coefficient of reliability of the test was 0.62. It showed that the test was reliable and the reliability was substantial. The data were analyzed by applying t-test formula. After the data were analyzed, the result of the study showed that t-observed (4.29) was higher than t-table (2.00) (t-observed > t-table) at the level of significance of α = 0.05 and at the degree of freedom (df) = 58. Therefore, the null hypothesis (Ho) is rejected and hypothesis alternative (Ha) is accepted. It means that there is significant effect of questioning strategies on students’ reading comprehension in narrative text.